Caracterización socioeconómica y productiva de las ganaderías bovinas en el cantón Palenque - Núñez Tovar, Ingrid Odaliz (2022)
In the characterization and typification, management, productive, social, economic and environmental variables are considered, since they allow knowing the critical points, strengths and the decision-making process in cattle production systems. The objective of the study was to characterize cattle ranches in the Palenque canton, from a socioeconomic and productive point of view in order to generate basic information for programs to support and promote cattle ranching, as well as serve as input for future research. This research was carried out in the canton of Palenque, province of Los Ríos. The survey method and the interview technique were used through the use of semi-structured questionnaires. The socioeconomic characterization shows that the average age of the producer of the Palenque canton is 61 years, with an average age of 27 years in livestock activity, and with primary education. Producers do not have the drinking water service for home and animal consumption. 41.1% of the producers are members of agricultural and livestock associations